Prospective and retrospective longitudinal studies of the growth, maturation and fitness of Polish youth active in sport - Malina, R. M.; Woynarowska, B.; Bielicki, T.; Beunen, G.; Eweld, D.; Geithner, C. A.; Huang, Y. C.; Rogers, D. M. (International Journal of Sports Medicine, 1997)
Results of three longitudinal studies of the growth, maturation and fitness of youth active in sport are summarized. Data include size attained and growth rates for height and body mass, secondary sex characteristics, skeletal age, age at peak height velocity, and two indicators of fitness, peak O2 uptake and power output at a heart rate of 170 bpm (PWC 170). The data for active youth are compared to local reference data and where appropriate to data from other European longitudinal studies. Allowing for variation in methodology and sampling, regular training in sport during puberty and the adolescent spurt does not influence size attained, growth rate, and the timing and progression of somatic, sexual and skeletal maturation in boys and girls. Active and nonactive boys and girls, respectively, do not differ significantly in the mean age at maximum growth in power output at a heart rate of 170 bpm. Boys active in sport, however, have a greater maximal gain in submaximal power output than nonactive boys. Analysis of ontogenetic allometry of peak oxygen uptake and stature and body mass indicate variation between individuals, and between boys of contrasting maturity status.